2022
DOI: 10.1039/d1ra09344d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bibliometric trends of microplastics and perfluoroalkyl and polyfluoroalkyl substances: how these hot environmental remediation research topics developed over time

Abstract: Bibliometrics point to the hottest areas of science and policy working to reverse the environmental impacts of PFAS and microplastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Since accumulation of PFAS in humans and animals was reported in 2001, active research has been conducted on this class of chemicals worldwide. According to Bakhshoodeh and Santos, the annual number of scientific publications on PFAS exceeded 100 in 2007 and reached ∼900 in 2020. Despite the proliferation of literature on PFAS, experimental data for basic physicochemical properties, including air/water partition coefficients ( K aw ), are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Since accumulation of PFAS in humans and animals was reported in 2001, active research has been conducted on this class of chemicals worldwide. According to Bakhshoodeh and Santos, the annual number of scientific publications on PFAS exceeded 100 in 2007 and reached ∼900 in 2020. Despite the proliferation of literature on PFAS, experimental data for basic physicochemical properties, including air/water partition coefficients ( K aw ), are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…8 As demonstrated in the rst of such MPs risk assessment to account for non-alignments between particle sizes in toxicity studies and the environment, 25 risk assessments that do not rescale particle concentrations (e.g., 26,43 ) dramatically underestimate risks. Owing to the recent rapid progression of the eld, 44 uncertainties in MPs ecological risk assessments have dropped precipitously in less than two years. In the rst such study, Koelmans et al 25 demonstrated the principle of non-alignments by characterizing risks in global freshwater ecosystems using the best available datawhich included highly uncertain particle size distributions.…”
Section: Characterizing Risks To Ecosystemsmentioning
confidence: 99%
“…24 To reduce uncertainties in future risk assessments, research is needed for quantitative particokinetics in mammals, adverse outcome pathways, in vitro to in vivo quantitative extrapolation, and a reliable toxicologically relevant metric (e.g., surface area) for predicting effects across a diversity of MP particle types. 32,50 Charting the path forward to regulatory emergence While scientic publications on MPs have increased exponentially in recent years 58 even being recognized as the hottest trending contaminant in Environmental Science & Technology in 2019 39 the same year that it surpassed per-and polyuoralkyl substances in total publications, 44 the transformation of information and data into knowledge has failed to progress at a proportional rate. Indeed, misconceptions and misunderstandings of what's known and unknown scientically about MPs continue to pervade both lay-persons and topicexperiences practitionersparticularly regarding risks to biota.…”
Section: Assessing Hazards Of Microplastics To Humans Through Drinkin...mentioning
confidence: 99%
See 2 more Smart Citations